Addition of antioxidant tempol in cryopreservation of alpaca (Vicugna pacos) sperm collected by deviation of the vas deferens - Gómez-Quispe, Oscar Elisbán (2016)
The aim of this study was to determine the effect of adding antioxidant Tempol in the individual and progressive motility of alpaca sperm at cooling and after thawing. Previously, the vas deferens was deviated in three males with suitable semen parameters. Sperm were collected three times per week and pooled to avoid the individual effect. The sample was distributed in four aliquots and placed in refrigeration to reach 5 °C in 2 h. The antioxidant was added in four concentrations: 0, 0.5, 1.0 y 1.5 mM when the aliquots reached 10 °C. The sperm were filled in 0.25 ml straws, placed over liquid nitrogen vapor by 6 min and then submerged. Individual motility at cooling was 55.1, 63.7, 52.8 and 45.0 (p<0.05) and after thawing 35.7, 42.3, 29.0 and 18.1% (p<0.05) for 0, 0.5, 1.0 and 1.5 mM Tempol, respectively. Progressive motility at cooling was 36.0, 42.4, 28.4 and 21.7 (p<0.05)and after thawing 24.4, 27.3, 21.1 and 15.8% for 0, 0.5, 1.0 y 1.5 mM Tempol, respectively (p<0.05). The individual and progressive motility was improved by addition of a low concentration of Tempol antioxidant (0.5 mM) during the criopreservation of alpaca sperms harvested by vas deferens.